THE INFLUENCE OF PROFESSIONAL MOTIVATION ON OCCURRENCE OF INTRAPERSONAL CONFLICT AMONG STUDENTS OF THE FIRST YEAR OF STUDY - Shulga, Galyna; Kolomiіets Lesia (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted to the problem of the influence of professional motivation on the emergence of intrapersonal conflict among students of the first year of studying the specialty “Preschool education”. The authors describe the reasons for choosing a pedagogical profession by students of the first year in accordance with the dominant motives, they to find out the essence of professional motivation and describ the peculiarities of the motivational sphere of the students of the first year of study. The greatest attention is paid to the clarification of the role of professional motivation in the formation of a future specialist, to the its impact on the development of professionalism of the individual, on educational and cognitive motives, motives for achieving success, emotional well-being of the individual. It is noted that the process of primary professionalization often causes students to experience uncertainty in their own future, to the negative emotional states and to the intrapersonal conflicts. Diagnosis and correction of the formation of professional motifs for students of the first year of study will improve the process of their adaptation to new conditions, will facilitate the structuring of personal meanings regarding the process of acquisition of education, the inclusion in the format of a new kind of activity - educational-professional. The article shows the results of the empirical study of the influence of professional motivation on the emergence of intrapersonal conflict of the students of the first year of study. It is established that students consider studying at a higher educational institution as a prospect of perfect mastery of a profession; It was found out that professional formation is associated with the possibilities of creative self-realization; educational-cognitive activity is not recognized as significant; the productivity of inclusion in educational activity depends on the time spent on independent work, the volume of mastering the educational material, the degree of self-organization, the success of overcoming obstacles; the low level of formation of the motives of students’ educational activity leads to a neutral attitude to the profession, situational interest in issues of professional growth, passivity and lack of initiative, the emergence of dissatisfaction with the life situation and subjective achievements; low level of professional motivation leads to internal conflicts among students, to increase emotional stress, decrease motives to succeed in studying and in professional development. The prospect of further scientific researches on the research problem, the definition of conditions for the prevention of intrapersonal conflicts among students of the first year of study, that determined by the failure or amorphous professional self-determination, the development of correctional programs for the psychological support of such students was determined.